Intra-articular MMP-1 in the spinal facet joint induces sustained pain and neuronal dysregulation in the DRG and spinal cord, and alters ligament kinematics under tensile loading - Ita, Meagan E.; Singh, Sagar; Troche, Harrison R.; Welch, Rachel L.; Winkelstein, Beth A. (Frontiers in Bioengineering and Biotechnology, 2022)
Chronic joint pain is a major healthcare challenge with a staggering socioeconomic burden. Pain from synovial joints is mediated by the innervated collagenous capsular ligament that surrounds the joint and encodes nociceptive signals. The interstitial collagenase MMP-1 is elevated in painful joint pathologies and has many roles in collagen regulation and signal transduction. Yet, the role of MMP-1 in mediating nociception in painful joints remains poorly understood. The goal of this study was to determine whether exogenous intra-articular MMP-1 induces pain in the spinal facet joint and to investigate effects of MMP-1 on mediating the capsular ligament’s collagen network, biomechanical response, and neuronal regulation. Intra-articular MMP-1 was administered into the cervical C6/C7 facet joints of rats. Mechanical hyperalgesia quantified behavioral sensitivity before, and for 28 days after, injection. On day 28, joint tissue structure was assessed using histology. Multiscale ligament kinematics were defined under tensile loading along with microstructural changes in the collagen network. The amount of degraded collagen in ligaments was quantified and substance P expression assayed in neural tissue since it is a regulatory of nociceptive signaling. Intra-articular MMP-1 induces behavioral sensitivity that is sustained for 28 days (p < 0.01), absent any significant effects on the structure of joint tissues. Yet, there are changes in the ligament’s biomechanical and microstructural behavior under load. Ligaments from joints injected with MMP-1 exhibit greater displacement at yield (p = 0.04) and a step-like increase in the number of anomalous reorganization events of the collagen fibers during loading (p ≤ 0.02). Collagen hybridizing peptide, a metric of damaged collagen, is positively correlated with the spread of collagen fibers in the unloaded state after MMP-1 (p = 0.01) and that correlation is maintained throughout the sub-failure regime (p ≤ 0.03). MMP-1 injection increases substance P expression in dorsal root ganglia (p < 0.01) and spinal cord (p < 0.01) neurons. These findings suggest that MMP-1 is a likely mediator of neuronal signaling in joint pain and that MMP-1 presence in the joint space may predispose the capsular ligament to altered responses to loading. MMP-1-mediated pathways may be relevant targets for treating degenerative joint pain in cases with subtle or no evidence of structural degeneration.